The interplay between neoantigens and immune cells in sarcomas treated with checkpoint inhibition - Anzar, Irantzu; Malone, Brandon; Samarakoon, Pubudu; Vardaxis, Ioannis; Simovski, Boris; Fontenelle, Hugues; Meza-Zepeda, Leonardo A.; Stratford, Richard; Keung, Emily Z.; Burgess, Melissa; Tawbi, Hussein A.; Myklebost, Ola; et al. (Frontiers in Immunology, 2023)
Sarcomas are comprised of diverse bone and connective tissue tumors with few effective therapeutic options for locally advanced unresectable and/or metastatic disease. Recent advances in immunotherapy, in particular immune checkpoint inhibition (ICI), have shown promising outcomes in several cancer indications. Unfortunately, ICI therapy has provided only modest clinical responses and seems moderately effective in a subset of the diverse subtypes. To explore the immune parameters governing ICI therapy resistance or immune escape, we performed whole exome sequencing (WES) on tumors and their matched normal blood, in addition to RNA-seq from tumors of 31 sarcoma patients treated with pembrolizumab. We used advanced computational methods to investigate key immune properties, such as neoantigens and immune cell composition in the tumor microenvironment (TME). A multifactorial analysis suggested that expression of high quality neoantigens in the context of specific immune cells in the TME are key prognostic markers of progression-free survival (PFS). The presence of several types of immune cells, including T cells, B cells and macrophages, in the TME were associated with improved PFS. Importantly, we also found the presence of both CD8+ T cells and neoantigens together was associated with improved survival compared to the presence of CD8+ T cells or neoantigens alone. Interestingly, this trend was not identified with the combined presence of CD8+ T cells and TMB; suggesting that a combined CD8+ T cell and neoantigen effect on PFS was important. The outcome of this study may inform future trials that may lead to improved outcomes for sarcoma patients treated with ICI.